Vier verrückte Schwestern - McKay, Hilary 1959- (dtv, 2001)
The four Conroy sisters spend a wild summer at the seaside with Big Grandma, who tries to break them of their reading habit by substituting fresh air and hard work for books and gets unexpected results.